Synthesis and Characterization of CaO-SiO2 Heterogeneous Catalyst of Blood Cockle Shells and Coconut Fiber Ash for Biodiesel Production from Crude Palm Oil - Nurhayati, Nurhayati; Muhdarina, Muhdarina; Linggawati, Amilia; Siregar, Siti Saidah (Universitas Gadjah Mada, 2025)
The utilization of sustainable and renewable materials, specifically CaO derived from blood clam shells and SiO2 extracted from coconut fiber, as catalysts for biodiesel production not only promotes waste valorization but also enhances catalytic efficiency, providing an eco-friendly and effective solution for biodiesel synthesis. The present study was synthesized and characterized CaO-SiO2 catalysts using the impregnation method with SiO2 content at 3, 5, and 7 wt.%. Characterization included surface area (BET), crystallinity and crystal size (XRD), chemical composition (XRF), functional groups (FTIR), and acidity-basicity (pyridine adsorption and titration). The maximum biodiesel yield of 96.29% was achieved under optimized conditions: 2 wt.% catalyst loading, 90-min reaction time, 60 °C temperature, and a 1:9 oil-to-methanol molar ratio, determined using response surface methodology (RSM). The synthesized biodiesel was evaluated according to ASTM D6751 standards, and its purity and methyl ester composition were analyzed using GC-MS. The results showed that the CaO-SiO2 catalyst achieved a biodiesel purity of 97.44%, higher than that obtained with unmodified CaO. This research successfully modified the CaO-SiO2 heterogeneous catalyst, enhancing its surface area and acidity, which led to an increase in the purity and yield of biodiesel synthesized from crude palm oil with high free fatty acid content.